Religiusitas Kualitas Pelayanan dan Etika Penggelapan Pajak - Teguh Erawati; Riski Adi Wibowo (Ekonomis: Journal of Economics and Business, 2023)
The purpose of this study was to show the effect of religiosity, service quality, and tax understanding on the ethics of tax evasion. The sample in this study consisted of 80 Tamansiswa University Bachelor of Accounting Students class 2019-2021. This research is quantitative research with a survey method. The data analysis method used in this study is multiple linear regression. The results of the analysis show that religiosity and tax understanding do not affect tax evasion ethics, service quality has a positive and significant effect on tax evasion ethics.